Mapping of Flood Inundation and Eco-hydraulic Analyses to Minimize Flood Discharge in Tributaries - Azmeri, Azmeri; Yulianur, Alfiansyah; Meilianda, Ella; Mubarak, Mubarak; Ziana, Ziana (Aceh International Journal of Science and Technology, 2023)
Eco-hydraulic analyses begin with the arrangement of tributaries. This research aimed to minimize the discharge of flood run-off downstream by involving the community's participation in planting vegetation on the river border. An eco-hydraulic analysis is divided into two stages: calculating eco-hydraulic analysis on the existing border width and on the design border width of 100 m and calculating the inundation height and flow velocity. Minimizing flood discharge in tributaries is important because the maximum discharge in the downstream tributaries will affect the discharge in large rivers. The data needed are the cross-section of the river, the distance between the sections, Manning's roughness number, the return period flood discharge, and the river's slope. The integration between topographic maps, watersheds, and flood water levels can display areas potentially affected by inundation floods so that the flood inundation limits and flood inundation areas can be calculated. This research examined proper eco-hydraulics design so that it could reduce discharge, identify locations prone to flooding, and describe the magnitude of the flood impact quantitatively. Based on the study's results, it was found that the arrangement of river borders can provide benefits for flood control measures; this arrangement is the basis for determining river border lines. The results eco-hydraulic method obtained the design border width of 100 m, the condition before the existing river border arrangement was carried out, the inundation height was 0.30 1.13 m, and after the river border arrangement, the discharge could be reduced to 113.09 209 m3/s and the inundation height is 0 0.31 m. Based on the research results, it is known that border arrangements can provide benefits for flood control measures.